Seedling quality, plant growth and fruit yield and quality of tomato (Solanum lycopersicum L.) in response to Trichoderma harzianum and arbuscular mycorrhizal fungi - Marais, D. (Diana) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.